O alcance do "compromisso de ajustamento de conduta", em sede de ação pública - Menezes, João Armando Costa (2009)
The focus of this work is the Conduct Settlement Commitment, an instrument which wards off or brings a Public Civil Action to an end, aiming its complete scope, more precisely, as regards its substantial contents delimitation and the validity control that should be carries on such contents, starting from the bear out that, as regards the judicial complexion, this Commitment is not an agreement (accordance), but, in fact, having the public-social and judicial concerns as its scope, it s a question of juridical action in the strict sense, related to the political-governmental action, contemplating the objective (utterly judicial) invigorated by the unavailability, from that cause, besides the formal limits imposed by law s regency, the contents (substantial composition) should fulfill the limits of its own objectives and the legally planed objectives In tune with the aims, it is visualized (imposed) the lawfulness control of the Conduct Settlement Commitment, the formal elements control as well as the substantial diction (object, reason and predetermined end) of this judicial action which directly affects the general concerns of social State body